2020
DOI: 10.3390/ma13020417
|View full text |Cite
|
Sign up to set email alerts
|

Solution Processable CrN Thin Films: Thickness-Dependent Electrical Transport Properties

Abstract: Thickness is a very important parameter with which to control the microstructures, along with physical properties in transition-metal nitride thin films. In work presented here, CrN films with different thicknesses (from 26 to 130 nm) were grown by chemical solution deposition. The films are pure phase and polycrystalline. Thickness dependence of microstructures and electrical transport behavior were studied. With the increase of films thickness, grain size and nitrogen content are increased, while resistivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The surface morphology of both as-deposited samples is shown in Figure 2 a,b; the investigated area in the SEM images is the same to make easier the comparison. The S50 film surface appears conformal constituted by small, irregularly shaped and uniformly distributed grains with well-defined boundaries which are figured out as darker line around the grains [ 50 , 51 ]. The S50 sample cross-section observation (see Figure 2 c) shows a homogeneous and dense growth of the thin film along the entire thickness.…”
Section: Resultsmentioning
confidence: 99%
“…The surface morphology of both as-deposited samples is shown in Figure 2 a,b; the investigated area in the SEM images is the same to make easier the comparison. The S50 film surface appears conformal constituted by small, irregularly shaped and uniformly distributed grains with well-defined boundaries which are figured out as darker line around the grains [ 50 , 51 ]. The S50 sample cross-section observation (see Figure 2 c) shows a homogeneous and dense growth of the thin film along the entire thickness.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the Cr 2p 3/2 peaks shift toward the lower energy level with increasing doping concentration of Ca 2+ (Figure 1f), which can be attributed to the electron screening effect [ 30 ] and relaxation effect. [ 31 ] It is well known that the electron binding energy is determined by the Coulomb force between the electron and the nucleus and the screening effect of other electrons, and the formation of electron holes can enhance the electron screening effect, resulting in the decrease in photoelectron binding energy. The electron relaxation can make partial electrons return to the ground state, accompanying the release of relaxation energy.…”
Section: Resultsmentioning
confidence: 99%
“…2) The temperature dependence of the electrical resistivity in CrN has been reported to exhibit contradictory conductivity. [5][6][7][8][9][10][11][12][13][14][15][16] Bhobe et al reported that bulk CrN transitions from an FM semiconductor to an AFM metal below T N , suggesting Mott-Hubbard-type semiconductor behavior. 5) By contrast, Inumaru et al found a discontinuity at the T N in the resistivity of CrN thin films grown on MgO(001) substrates by pulsed laser deposition (PLD), indicating metallic behavior.…”
Section: Introductionmentioning
confidence: 99%